Justiça intergeracional e superação do conceito de sustentabilidade através da Parresía - Kury, Francisco Ricardo Cichero (Universidade do Vale do Rio dos Sinos, 2017)
Sustainability is a problematic concept that has obscured the legitimate concept of intergenerational justice. Environmental Law will not obtain appreciable results so long as sustainability is considered the first foundation of a science that needs to approach philosophy to generate effective compliance with the understanding of intergenerational justice. Adopting intergenerational justice as the foundation of Environmental Law, which is supported by Human Rights, changes the idea of sustainable development for equitable development for the use and transformation of natural wealth among peoples. For this task the concept of parrhesia inspires a new point of view for legal communication that must be strengthened to denounce what sustainability is part of the social contagion that reaches the right to make it inefficient. Parresía means a legitimate posture to advocate for the humanity that is understood as a human family within an Environmental Law Philosophy that will be based on the concept of physis. All this conception will enter into international law to interpose in the dialogue between nations the concept of intergenerational justice.
Keywords: Sustentabilidade; Justiça intergeracinal; Parresía; Contabescência social; Filosofia do direito ambiental; Direito ambiental; Sustainability; Justice; Parrhesia; Social contagion; Environmental law philosophy; Environmental law; ACCNPQ::Ciências Sociais Aplicadas::Direito